DENDA DALAM BAI’ BITSAMAN AJIL MENURUT FIQIH DAN FATWA DEWAN SYARIAH NASIONAL (DSN) - Aulil Amri (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This study is to analyze the application of fines to customers who delay payments on purpose or do not have the will and good faith to pay their debts. Legal fines for capable people who delay payment according to fiqh and fatwa DSN-MUI Number 17 / DSN-MUI / IX / 2000 are permissible. The fatwa explained that customers who could be fined were customers who delayed payments deliberately and / or did not have the will and good faith to pay their debts. While customers who are unable or unable to pay due to force majeure may not be penalized. In addition to the fatwa of the DSN MUI, the fines determined are also based on ba‘i bitsaman ajil financing agreement at Baitul Mal / Qiradh that has been agreed by both parties. The results showed that some syari’ah banking transactions are in accordance with Islamic syari’ah, but there is still practice going on in the field of the application of fines imposed in general, not looking at the feathers for both capable and unable customers. Finally, fines will accumulate every month plus piles of arrears. This is really unfortunate because it should be given to those who cannot afford to be given tough time to pay for this in accordance with the fatwa DSN-MUI Number 17 / DSN-MUI / IX / 2000. In the future, the Syari’ah Supervisory Board can take firm action on this matter.